THERMODYNAMIC STUDY OF METHYLENE BLUE DYE ADSORPTION USING KAPOK HUSK - Hamdhan Fathony; Suci Wulandari; Putri Ramadhani; Rahmiana Zein; Deswati (JURNAL KATALISATOR, 2023)
This research discusses the thermodynamics of methylene blue(MB) adsorption using kapok husk (KH) and kapok huskmodified with citric acid (CA-KH). Both biosorbents obtained thermodynamic results with a negative value of the change in Gibbs energy (∆G), indicating that the adsorption process took place spontaneously, a negative value on enthalpy (∆H), indicating the adsorption process was an exothermic process, and a negative entropy value (∆S) indicating an increase The regular distribution of methylene blue dye on the surface during the adsorption process is proven by the results of SEM photo analysis at 3000x magnification with the distribution of methylene blue dye on the surface of the two biosorbents..